THE ROLE OF ISLAMIC FINANCIAL SYSTEM ACTIVITIES TOWARDS ECONOMIC GROWTH - Ibrahim Musa Gani; Zakaria Bin Bahari (International Journal of Accounting, Finance and Business, 2020)
Finance has generally used various straits through which it affects economic growth. This study identified the main channels of Islamic financial development transmitting economic growth. The study also analysed the channels and showed how channels for determining economic growth are used by Islamic financial development. To do this, the study adopted a library research method. The study concludes that investment quantity or capital accumulation, and capital efficiency or capital productivity from Islamic financial activities are the main channels through which the Islamic financial system uses to increase economic activity in a country, and thus achieve economic growth. Consequently, the study suggested that Islamic financial institutions use the funds available to them wisely to finance potentially viable, short-term or long-term successful investments. The report also suggested that Islamic financial institutions have appropriate oversight and efficient capital and risk management.